Konsep Homoseksual Dipandang Dari Perspektif Psikologi Kontemporer dan Psikologi Islam - Assy Syaffa Humayya (Jurnal Psikologi Terapan, 2019)
Homosexuality is a familiar issue in society, the issue as it has become the reality of life today, in Islam homosexual called as liwath. both terms can be defined as sexual orientation behavior directed by individuals of the same sex, homosexual behavior is regarded as a sexual deviation by the West's view while in Islamic view the behavior of liwath is regarded as a bad and transcending act, as for the purpose of this paper is to discuss homosexual behavior in Western and Islamic perspectives and inform the reader about the effects of homosexual behavior.